The Strategy of Gorontalo Police Service in Improving Community Vaccination Discipline in the Era of the Covid-19 Pandemic - ahmad rizak daud; Arifin Tahir; Djamila Podungge (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine and analyze the strategy of Gorontalo Police Service in improving community vaccination discipline in the Covid-19 pandemic era. This type of research is descriptive qualitative. Data collection techniques through interviews, observation and documentation studies. Data analysis techniques through data reduction, data presentation, and data verification. The results showed that the strategy of Gorontalo Police Service was running well through the Determination of Service Standards, Information and Openness, Preference and Counseling, Leading Personnel Practices, Effective Complaints Unit, Use of Information and Communication Technology. The strategy of Gorontalo Police Service has been able to improve community vaccination discipline in the Covid-19 pandemic era, but daily achievements have not met the expected target. Constraints faced 1) Limited human resources, 2) Lack of mobilization facilities, 3) Lack of public awareness for vaccination. It is recommended that the Gorontalo Police Resources Department carry out technical guidance on an ongoing basis for the management and administration of Covid-19 vaccination services in Gorontalo Regency. People who have received vaccinations are expected to remain disciplined in maintaining the 5M health protocol, washing hands, wearing masks, maintaining distance, avoiding crowds and limiting mobility. People who have not received vaccinations are expected with self-awareness to immediately go to referral places to get vaccination services